Mathematical modeling of ecological safety on the basis of collective remote access databases: on the example of landslides of the Middle Dnieper - Prikhodko, Vyacheslav (Transfer of innovative technologies, 2021)
A mathematical model for the calculation of the main indicators of environmental safety on the example of landslides of the Middle Dnieper region. The model with the data of regime observations of the system of ecological monitoring, gives the chance to estimate a situation for the investigated period, to define the basic dangerous indicators and on them to make the forecast (in the form of diagnostics of mathematical model on change of sizes of parameters). ). Also assess the environmental risks for making sound management decisions to control the quality of the environment